Effectiveness of autoclaving in sterilizing reusable medical devices in healthcare facilities - Gopal Panta; Ann K Richardson; Ian C Shaw (Journal of Infection in Developing Countries)
Medical devices are sterilized before being used for invasive clinical procedures such as surgery, to prevent pathogen transfer. Failure to sterilize medical devices properly presents a risk of healthcare-associated infections. Studies and reports have indicated that inadequately sterilized medical devices are one of the causes of a higher rate of healthcare-associated infections in developing countries. Steam sterilization (autoclaving) is the most widely used method for sterilization and is considered the most robust and cost-effective method for sterilization of medical devices. The effectiveness of steam sterilization can be measured using biological indicators. A literature search was undertaken to understand the effectiveness of autoclaving in sterilizing reusable medical devices in healthcare facilities across the globe. Studies using biological indicators for measuring the effectiveness of autoclaving were obtained. Failures of steam sterilization practices were identified and discussed as a means of identifying factors that might be associated with the ineffectiveness of steam sterilization practices between different countries. The number of studies measuring the effectiveness of steam sterilization is small, and few evaluate the effectiveness of steam sterilization specifically in developing countries. There are fewer studies on higher level healthcare facilities than dental facilities. More evidence about the effectiveness of autoclaving in healthcare facilities is needed to draw firm conclusions, but the data suggest that there are inadequacies in autoclave procedures and operator education.